Analisis Dosis dan Efek Neurofarmakologi Infusa Daun Tamarindus indica (L.) pada Hewan Uji Mencit - Haryanto Haryanto; Sahrul Gunawan; Atiqah Ainunnisa' Andy Putri; Andi Eka Purwanti; Salsabila Ramadhani; Hilyah Muthiah; Saskiah Adiajuns; Sukma Febrianti sukri; Nur Aqila Novi Dwiyanti; Nurul Fazilawati Ode (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
This study aims to investigate the effects of tamarind leaf extract (Tamarindus indica L.) on neuropharmacological activity in mice using calculated percentages of responses based on the parameters PSM, SSSP, DSSP, SL, RO, SM, PSL, and ANA. This research was conducted as a laboratory experiment using a completely randomized design (CRD) with three treatment concentrations: 1%, 2%, and 4%. Observations were performed to assess the percentage of activity produced by each sample concentration, followed by descriptive–quantitative analysis to determine the dose–response pattern. The results showed that tamarind leaf extract produced varying responses across concentrations. The SSSP, ANA, and RO effects demonstrated increased activity at the 2% concentration, whereas other parameters (PSM, PSL, SM, SL, and DSSP) showed decreased activity. Interestingly, the SSSP parameter exhibited a positive dose–response pattern with the highest activity of 55.84% at 2%. Overall, the effectiveness of tamarind leaf extract depends on the concentration level. The 2% concentration appears to be the optimal dose for several neuropharmacological effects, while the 4% concentration was most effective only for SSSP. These findings highlight the importance of multi-concentration testing to determine effective dosing of natural products for biological applications and the need for further investigation.